PENGGUNAAN VIDEOSCRIBE UNTUK MENINGKATKAN KEMAMPUAN PENGUASAAN KOSAKATA BAHASA MANDARIN SMA ADISUCIPTO KUBURAYA - Sutiyarti, Sutiyarti; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract Vocabulary is very important in language learning becouse only students who have mastered vocabulary can express their meaning come out. If you don?t learn vocabulary well, you may say something wrong. Using videoscribe makes classroom teaching more convenient, deepen students memory of teaching content, and it is a more interesting way to learn. The purpose of this study is to understand whether the use of videoscribe can improve students mastery in chinese vocabulary. The research used videoscribe in second grade students of Adisucipto High School. The results showed that the comparison between the post-test and the pre-test in the experimental class increased by 47%. Meanwhile, the comparison between the post-test and the pre-test in control class only increased 20%. Thus, we can conclude that the experimental class is better than control class in mastering Chinese vocabulary. In short, using Videoscribe in the teaching-learning process can improve studentsmastery in Chinese vocabulary. Keywords: Mastery, Videoscribe, Vocabolary